2011
DOI: 10.1242/dev.061192
|View full text |Cite
|
Sign up to set email alerts
|

The heart endocardium is derived from vascular endothelial progenitors

Abstract: SUMMARYThe embryonic heart is composed of two cell layers: the myocardium, which contributes to cardiac muscle tissue, and the endocardium, which covers the inner lumen of the heart. Whereas significant progress has been made toward elucidating the embryonic origins of the myocardium, the origins of the endocardium remain unclear. Here, we have identified an endocardiumforming field medial to the cardiac crescent, in a continuum with the endothelial plexus. In vivo live imaging of quail embryos revealed that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
111
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(123 citation statements)
references
References 48 publications
11
111
1
Order By: Relevance
“…Furthermore, BMP expression is sufficient to initiate nfatc1 expression in a subset of vascular endothelial cells in hand2 mutants. These results support a model where endocardial cells are derived from vascular endothelial lineage, in agreement with other recent studies (Bussmann et al, 2007;Schoenebeck et al, 2007;Milgrom-Hoffman et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, BMP expression is sufficient to initiate nfatc1 expression in a subset of vascular endothelial cells in hand2 mutants. These results support a model where endocardial cells are derived from vascular endothelial lineage, in agreement with other recent studies (Bussmann et al, 2007;Schoenebeck et al, 2007;Milgrom-Hoffman et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Endocardial cells and vascular endothelial cells of blood vessels express many of the same molecular markers, which suggests a common origin of both cell types. Indeed, recent evidence argues that endocardial cells are derived from vascular endothelial progenitors (Misfeldt et al, 2009;Milgrom-Hoffman et al, 2011). However, endocardial cells exhibit distinct migratory behavior and express specialized markers such as nfatc1 (de la Pompa et al, 1998), which shows that the endocardial and vascular endothelial cells of blood vessels are biochemically distinct.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, inactivation of Nkx2-5 by Isl1-Ires-Cre consistently resulted in perinatal (P1) lethality due to OFT septation defects. Both Isl1-Cre and Isl1-Ires-Cre lines mediate early recombination very early in the SHF progenitors (Cai et al, 2003, Yang et al, 2006Sun et al, 2007); however, we found that Isl1-Cre-mediated recombination is far more efficient in the SHF than Isl1-Ires-Cre (Milgrom-Hoffman et al, 2011). Consistent with Isl1-Cre cell lineage studies (supplementary material Fig.…”
Section: Nkx2-5supporting
confidence: 88%
“…Cardiac contraction and blood flow are intimately associated and cannot be decoupled easily in the developing zebrafish ventricle by genetic means. Although endocardial cells might arise from either vascular endothelial cells or cardiac progenitors, they are a type of endothelial cell and are highly sensitive to flow (Bussmann et al, 2007;Kattman et al, 2006;Milgrom-Hoffman et al, 2011;Moretti et al, 2006;Vermot et al, 2009). We used an in vitro system to apply low-magnitude flow to endothelial cells to model endocardial, cilia-dependent flow responses and found that flow stimulated Notch1, Efnb2 and Nrg1 expression in the absence of myocardially derived factors or circulating factors in the bloodstream.…”
Section: Discussionmentioning
confidence: 99%